Thermal design of a finned double pipe heat exchanger for methanol cooling - Pérez Sánchez, Amaury; Valero Almanza, Greisy Ivety; Ranero González, Elizabeth; Pérez Sánchez, Eddy Javier (Nexo Revista Científica, 2021)
In the present work, the thermal design of a double tube heat exchanger with finned tubes for methanol cooling was performed. Two sensitivity studies were also carried out to determine the influence of an increase in both the feed rate (mc) and the methanol inlet temperature (T1) on four exchanger design parameters. The designed heat exchanger will have a fin efficiency of 0.236, a cleaning factor of 0.60, a heat transfer area under fouling conditions of 20.53 m2, and a total number of hairpins equal to three to meet the thermal duty of the system. Both the calculated pressure drop of the cooling water (5,880.39 Pa) and the methanol (70,711.91 Pa) are below the maximum limits established by the process. A pumping power of 17.52 W and 160.62 W is required to pump the cooling water and methanol respectively. It is recommended that mc does not exceed 5,800 kg/h, while T1 can be increased up to 80 ºC without negatively affecting the pressure drop of the cooling water, although this increases the pumping power of the cooling water.Caída de presión